Pengembangan Media Komik Digital Berbahasa Jerman Cerita Rakyat Batak Toba “Raja Si Opat Ama” Mengunakan bantuan Aplikasi Next GToon - Chyntia Pamela Siregar; Laili Insyirah Nasywa; Novyar Ardhana Pasaribu; Emirah Rezqa Mujahidah; Christy Aprilia Simamora; Epa Rahmayani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study focuses on the development of a digital comic medium that features the Batak Toba folktale titled “Raja Si Opat Ama” in German. The development process utilizes the Next GToon application to facilitate the creation of engaging and interactive digital comics. The primary aim of this research is to preserve the cultural heritage of Batak Toba while introducing it to the international community, particularly German speakers. During its development, the folktale was translated into German and visualized in the form of a digital comic. The illustrations, storyline, and dialogues were designed by considering local cultural aspects to maintain authenticity while ensuring that they are easily understood by foreign readers. With this medium, it is expected that readers can learn about Batak Toba culture in an enjoyable and modern way. The final product is a digital comic that serves not only as entertainment but also as a tool for cultural and language learning.